2004
DOI: 10.1038/sj.onc.1207439
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of p120ctn and E-cadherin loss characterize lobular breast carcinoma from preinvasive to metastatic lesions

Abstract: Accumulating evidences indicate that p120 catenin, a member of the E-cadherin (E-CD)/catenin adhesion complex, plays a role in tumor invasion. To establish the expression pattern of p120 in breast cancer, we analysed 326 breast tissue biopsies by tissue microarray. Most of the lobular tumors (88%) showed exclusive cytoplasmic localization, and 6% of them also had p120 nuclear staining. Cytoplasmic p120 strongly associated with complete loss of E-CD and b-catenin not only in lobular carcinoma and its metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 40 publications
15
136
2
1
Order By: Relevance
“…Loss of E-cadherin expression is accompanied by a loss of β-catenin expression and a diffuse scattering of Tables 1 and 2 the E-cadherin binding protein p120-catenin over the whole cytoplasm in both cell lines ( Figure 5C). Aberrant cytoplasmic localization of p120-catenin, which is virtually never observed in ductal mammary carcinomas [4], was also clearly evident in IPH-926 tumours grown in SCID mice and the ILBC of the corresponding patient ( Figure 5D). Both cell lines are also ErbB2-negative ( Figure 5A).…”
Section: Comparison Of Iph-926 and Mda-mb-134mentioning
confidence: 80%
See 1 more Smart Citation
“…Loss of E-cadherin expression is accompanied by a loss of β-catenin expression and a diffuse scattering of Tables 1 and 2 the E-cadherin binding protein p120-catenin over the whole cytoplasm in both cell lines ( Figure 5C). Aberrant cytoplasmic localization of p120-catenin, which is virtually never observed in ductal mammary carcinomas [4], was also clearly evident in IPH-926 tumours grown in SCID mice and the ILBC of the corresponding patient ( Figure 5D). Both cell lines are also ErbB2-negative ( Figure 5A).…”
Section: Comparison Of Iph-926 and Mda-mb-134mentioning
confidence: 80%
“…They lack expression of E-cadherin [2] and this serves as a supportive parameter in their clinical diagnosis [1]. Loss of E-cadherin expression is always accompanied by a loss of β-catenin expression and is frequently associated with aberrant cytoplasmic localization of the Ecadherin binding protein p120-catenin in ILBCs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This LOH definitely accompanies mutations in cases of invasive lobular carcinoma, however, the classic pattern of LOH coupled with inactivating mutations in lobular carcinoma in situ has not been confirmed. In the other 50% loss of E-cadherin is attributed to epigenetic events, with hypermethylation of the E-cadherin promoter region at CpG islands being one of the most important ones and possibly occurring very early, even at the stage of atypical lobular hyperplasia (Sarrio et al, 2004;Shibata et al, 2004;Knudsen and Wheelock, 2005;Mastracci et al, 2005).…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
“…Although treatment for stage-matched ductal versus lobular carcinomas is similar [9], several studies have shown that ILC is a distinct entity of breast cancer that differs from IDC not only in histological and clinical features [10,11] but also in the risk factors [12], genomic profiles [13], global transcription programs [14], immunophenotype [15] and response to systemic therapy [11,16,17]. Such studies suggest that lobular tumour development and progression may follow a distinct pathway from ductal tumours.…”
Section: Introductionmentioning
confidence: 99%